Creating Good Environment and Building for People with Special Needs: From Definition to Application of Guiding and Warning Blocks - Ali Rahmat (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of writing this paper is to discuss the definition and application of guiding blocks. We analyzed and searched the literature to discuss the definition and application of guiding blocks. This paper can be used as a reference for practitioners in the application of tactile guiding blocks.